Primary Education and Inclusion: A Study of Social Representations - Garnique Castro, Felicita; Dirección de Educación Especial, Secretaría de Educación Pública, SEP, Ciudad de México, México (Editorial Pontificia Universidad Javeriana, 2012)
This paper is the result of Social representations about inclusion. A review from the field of primary education, a research project that aimed to identify the social representations about Inclusion of diversity at schools present among teachers, management and supervisors in primary educations in Mexico. This paper presents the analysis of the discourse of those (female) teachers called collaborating teachers. A qualitative methodology is applied to analyze the circumstances in which the social representations of these teachers are produced and go round, and what problems they face when incorporating inclusion in the classroom. The results show how social representations guide the teacher's attitudes, values, and behavior in the classroom.